Comb-assisted cavity ring-down spectroscopy of a buffer-gas-cooled molecular beam. Issue 25 (8th June 2016) - Santamaria, Luigi; Sarno, Valentina Di; Natale, Paolo De; Rosa, Maurizio De; Inguscio, Massimo; Mosca, Simona; Ricciardi, Iolanda; Calonico, Davide; Levi, Filippo; Maddaloni, Pasquale
Abstract : We demonstrate continuous-wave cavity ring-down spectroscopy of a partially hydrodynamic molecular beam emerging from a buffer-gas-cooling source. Abstract : We demonstrate continuous-wave cavity ring-down spectroscopy of a partially hydrodynamic molecular beam emerging from a buffer-gas-cooling source. Specifically, the ( ν 1 + ν 3 ) vibrational overtone band of acetylene (C2 H2 ) around 1.5 μm is accessed using a narrow-linewidth diode laser stabilized against a GPS-disciplined rubidium clock via an optical frequency comb synthesizer. As an example, the absolute frequency of the R (1) component is measured with a fractional accuracy of ∼1 × 10 −9 . Our approach represents the first step towards the extension of more sophisticated cavity-enhanced interrogation schemes, including saturated absorption cavity ring-down or two-photon excitation, to buffer-gas-cooled molecular beams.